Search for new phenomena in final states with b-jets and missing transverse momentum in √s=13 TeV pp collisions with the ATLAS detector - Aad, Georges; Bartels, Falk; Czurylo, Marta; Dittmeier, Sebastian; Dunford, Monica; Franchino, Silvia; Klassen, Martin; Krishnan, Anjali; Mkrtchyan, Tigran; Ott, Philipp; Rassloff, Damir Fabrice; Schöning, André; et al. (Journal of high energy physics, 2021)
The results of a search for new phenomena in final states with b-jets and missing transverse momentum using 139 fb−1 of proton-proton data collected at a centre-of-mass energy $$ \sqrt{s} $$= 13 TeV by the ATLAS detector at the LHC are reported. The analysis targets final states produced by the decay of a pair-produced supersymmetric bottom squark into a bottom quark and a stable neutralino. The analysis also seeks evidence for models of pair production of dark matter particles produced through the decay of a generic scalar or pseudoscalar mediator state in association with a pair of bottom quarks, and models of pair production of scalar third-generation down-type leptoquarks. No significant excess of events over the Standard Model background expectation is observed in any of the signal regions considered by the analysis. Bottom squark masses below 1270 GeV are excluded at 95% confidence level if the neutralino is massless. In the case of nearly mass-degenerate bottom squarks and neutralinos, the use of dedicated secondary-vertex identification techniques permits the exclusion of bottom squarks with masses up to 660 GeV for mass splittings between the squark and the neutralino of 10 GeV. These limits extend substantially beyond the regions of parameter space excluded by similar ATLAS searches performed previously.
Im Titel steht der Buchstabe s unter dem Wurzelsymbol
The ATLAS Collaboration: G. Aad, F. Bartels, M.M. Czurylo, S.J. Dittmeier, M. Dunford, S. Franchino, M. Klassen, A. Krishnan, T. Mkrtchyan, P.S. Ott, D.F. Rassloff, A. Schoening, H-C. Schultz-Coulon, R. Stamen, P. Starovoitov, L. Vigani, S.M. Weber, M. Wessels, X. Yue [und viele weitere]
Gesehen am 27.07.2021